Extruder for food product (otak–otak) with heater and roll cutter - Dol Baharin, Muhammad Zulhusmi; Abd. Manan, Abdul Shukur; Baharom, Muhamad Hafizuddin; Hassan, Mohd Fahrul; Che Mat, Nor Ain; Ahmad, Muhamad Nurhisham (Penerbit UTHM, 2017)
Food extrusion is a form of extrusion used in food industries. It is a process by which a set of mixed ingredients are forced through an opening in a perforated plate or die with a design specific to the food, and is then cut to a specified size by blades [1]. Summary of the invention principal objects of the present invention are to provide a machine capable of continuously producing food products having an’ extruded filler material of meat or similarity and an extruded outer covering of a moldable food product, such as otak-otak, that completely envelopes the filler material.